ANALISIS ATAS TERBENTUKNYA MAZHAB FIKIH, ILMU KALAM, DAN TASAWUF SERTA IMPLIKASINYA DALAM MEMBANGUN UKHUWAH ISLAMIYAH - Hidayat, Tatang; Firdaus, Endis (AL-ISHLAH: Jurnal Pendidikan, 2018)
Sejarah terbentuknya mazhab fikih, ilmu kalam, dan tasawuf dalam Islam sangat penting untuk dibahas, serta memiliki keunggulan dari segi menambah wawasan keislaman dalam menghadapi perbedaan di tengah-tengah umat. Tujuan pembahasan ini dalam rangka menganalisis fakta dan perkembangan problematika sejarah terbentuknya mazhab fikih, ilmu kalam, dan tasawuf serta implikasinya dalam membangun ukhuwah Islamiyah. Pembahasan ini menggunakan pendekatan kualitatif dan metode studi literatur. Berdasarkan hasil pembahasan, kelahiran mazhab fikih dengan pola dan karakteristik tersendiri ini, tak pelak lagi menimbulkan berbagai perbedaan pendapat dan beragamnya produk hukum yang dihasilkan. Para tokoh imam mazhab seperti Imam Hanafi, Imam Maliki, Imam Syafi’i, dan Imam Hambali, masing-masing menawarkan teori, kaidah-kaidah ijtihad dan kerangka metodologi yang menjadi pijakan mereka dalam menetapkan hukum. Adapun sejarah ilmu kalam, berawal dari peristiwa tahkim yang kemudian menimbulkan tiga aliran teologi dalam Islam, yaitu aliran Khawarij, Murji’ah, dan Mu’tazilah. Sementara, sejarah perkataan tasawuf baru dikenal setelah abad ketiga hijriah, tetapi kandungan ajaran tasawuf sudah ada pada diri Nabi dan para sahabat beliau. Walaupun demikian, pendapat ulama tentang sejarah pendirian gerakan tasawuf masih berbeda-beda. Implikasnya, pembahasan ini akan semakin membuka wawasan pemikiran dan akan lebih bijak lagi ketika menghadapi perbedaan di tengah-tengah umat demi terwujudnya ukhuwah Islamiyah.The history of the establishment of fikih, kalam, and Sufism schools of thought (mazhab) in Islam is considered as a crucial thing to discuss and it in fact has advantages in terms of increasing Islamic insight in facing the diversity among people. The purpose of this present study is to analyze the facts and the problem development of the history of the establishment of fikih, kalam, and sufism schools of thought and their implications in building ukhuwah Islamiyah. This present study employed a qualitative approach and literature study methods. Based on the results of the discussion, the establishment of fikih school of thought along with its own patterns and characteristics inevitably led to various differences of opinion and the variety of legal products. The schools of thought (Imam mazhab) figures such as Imam Hanafi, Imam Maliki, Imam Syafi’i, and Imam Hambali, postulated their own theories, rules of ijtihad and methodological frameworks as the basis in establishing a binding ruling of religious matters. In particular, as for the history of the science of kalam, it was started in the time of tahkim event which later led to the three schools of theology in Islam covering the Khawarij, Murji'ah, and Mu’tazilah. On the other hand, the history of Sufism was only known after the third century of hijriah, even though the teaching of Sufism was already embodied in the Prophet and his companions. Nevertheless, the Islamic scholars had different opinions regarding the history of the establishment of Sufism movements. In fact, the implication of this study will open up more insight and it will promote a wise attitude in facing different opinions in the midst of the people in order to realize Islamic Unity (ukhuwah Islamiyah).